Development of a Geography Module Based on Group Investigation Integrated with High Order Thinking Skills on Exogenous Material to Improve Critical Thinking Skills of High School Students - Agus Supriyanto; Muhammad Nursa’ban (Postgraduate, University of Mataram, 2025)
Critical thinking skills can be facilitated through learning with a group investigation (GI) model. Therefore, a teaching module integrated with high order thinking skills is needed to support the learning process. The purpose of this study was to determine the analysis of teacher and student needs for geography module based on group investigation integrated with high order thinking skills, module validity, level of practicality, and effectiveness of the module in improving students' critical thinkig skills. This study is a development research. Data were analyzed using qualitative and quantitative methods. Qualitative descriptive analysis was used to analyze data on needs, validity, and practicality of the module, while quantitative analysis was used to test the effectiveness of the module. The results of the needs analysis showed that teachers needed for geography module based on group investigation integrated with high order thinking skills, and students needed interesting and easy-to-understand learning media. Expert validation showed that the module had a validity index of 93.5% with a very valid category. The practicality level of the module reached 81% with a practical category. Effectiveness testing using the independent sample t-test produced a sig value. (2-tailed) of 0.000 (<0.05), which shows that the module is effective in improving students' critical thinking skills. The conclusion of this study is that the for geography module based on group investigation integrated with high order thinking skills is valid, practical, and effective in improving students' critical thinking skills in exogenous material.